A Cu2 - x S / Graphene composite absorbing material and preparation method thereof

By uniformly adhering Cu2-xS nanocrystals on Graphene, forming Cu2-xS/Graphene composite wave absorbing material, the problem of Cu2-xS nanocrystal agglomeration is solved, and the efficient electromagnetic wave absorption and wideband performance of the material are achieved.

CN116285885BActive Publication Date: 2025-04-22ZHEJIANG LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310110749.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-04-22
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

Existing absorbing materials have shortcomings in stability, compatibility and absorption properties, especially Cu2-xS nanocrystal particles are prone to agglomeration and their dispersion needs to be improved.

Method used

Cu2-xS/Graphene composite absorbing material is used to uniformly attach Cu2-xS nanocrystals to a single layer of two-dimensional Graphene to improve the dispersion of the nanocrystals, and the absorbing performance of the material is regulated by regulating the molar ratio between Cu2+/CuS.

Benefits of technology

The uniform dispersion of Cu2-xS nanocrystals is achieved, the interfacial polarization characteristics and dielectric properties of the material are improved, and the electromagnetic wave reflection loss performance and wide-band wave absorption capacity are excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116285885B_ABST
    Figure CN116285885B_ABST
Patent Text Reader

Abstract

The invention discloses a Cu 2‑x The S / Graphene composite wave absorbing material and the preparation method thereof include: mixing a sulfur-containing precursor solution and a copper source, and washing the sample by centrifugation to prepare a CuS dispersion; preparing a graphene organic stripping solution by ultrasonic method; mixing the graphene organic stripping solution with the CuS dispersion solution in a certain proportion, and adding a guest cation Cu 2+ and reducing agent, centrifuge and wash to obtain Cu 2‑ x S / Graphene composite absorbing material, in which Cu 2‑x S particles are uniformly attached to the monolayer 2D Graphene, where Cu 2‑x The mass ratio of S to Graphene is 1:(0.01-0.15), and the value range of x is 0≤x≤1, so as to meet the requirements of "thin, light, wide and strong" for the absorbing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials and particularly relates to a Cu 2-x S / Graphene composite absorbing material and preparation method thereof. Background Art

[0002] With the development of electronic information technology, the widespread use of high-frequency equipment has brought convenience to society, but also brought harm from electromagnetic radiation. The impact of electromagnetic radiation and electromagnetic interference on the human body, industry, commerce, etc. has led to a sharp increase in the demand for the application of absorbing materials.

[0003] Electromagnetic wave absorbing material is a material that can attenuate incident electromagnetic waves through its own absorption effect. The principle is to convert electromagnetic waves into other forms of energy such as heat energy, electrical energy or mechanical energy through dielectric loss and consume them.

[0004] Electromagnetic wave absorbing materials are widely used in civil, military, aerospace and other fields, and have become a research hotspot in electromagnetic shielding, electromagnetic stealth and anti-electromagnetic radiation interference. In addition, the application of absorbing materials in microwave communications, microwave darkrooms, computers, medical diagnosis and treatment, and household appliances can greatly reduce the interference of electromagnetic waves on equipment and the harm to the human body.

[0005] At present, the absorbing materials on the market include magnetic loss type absorbing materials, electric loss type absorbing materials, plasma absorbing materials, etc. Among them, although magnetic loss type absorbing materials represented by ferrite and carbonyl iron powder have the advantages of high magnetic permeability and high impedance matching, they have the disadvantages of high density and poor temperature stability. Although electric loss type absorbing materials represented by conductive polymers and carbon-based absorbers have the characteristics of high conductivity, low density and high temperature resistance, they have poor impedance matching and narrow absorption bandwidth. Plasma absorbing materials have the advantages of thin coating, wide bandwidth and strong absorption, but their radioactive elements are harmful to the human body, which limits their practical application in the field of absorbing.

[0006] Therefore, seeking a new type of absorbing material with good stability, strong compatibility, light weight and high absorption has become a hot topic of research at this stage.

[0007] Patent document CN 108862366 A discloses a sheet Cu 2-x Application of S nanocrystals as microwave absorbers and preparation methods thereof, wherein the flake Cu 2-x When S (0≤x≤1) nanocrystals are used as microwave absorbers, when the mass filling rate is 20%-60%, they have good electromagnetic wave reflection loss performance, but Cu 2-x S nanocrystalline particles are easy to agglomerate and their dispersibility needs to be further improved. Summary of the invention

[0008] In view of the above, the object of the present invention is to provide a Cu 2-x S / Graphene composite absorbing material and preparation method thereof to improve Cu 2-x The dispersibility of S nanocrystals meets the requirements of "thin, light, wide and strong" for absorbing materials.

[0009] To achieve the above-mentioned purpose of the invention, a Cu 2-x S / Graphene composite absorber, Cu 2-x S particles are uniformly attached to the monolayer 2D Graphene, where Cu 2-x The mass ratio of S to Graphene is 1:(0.01-0.15), and the value range of x is 0≤x≤1.

[0010] The Cu 2-x In S / Graphene composite absorber, Graphene plays a role in improving Cu 2-x S nanocrystal dispersion, improve the material interface polarization characteristics, dielectric properties; Cu 2-x S by Cu 2+ , CuS and a reducing agent react to obtain Cu 2-x The change of the content of copper ion vacancies in S will change the dielectric properties of the material, thereby affecting the electromagnetic wave reflection loss ability of the material. 2+ The molar ratio of Cu / CuS can be adjusted 2-x The absorbing properties of S / Graphene composite absorbing material.

[0011] Among them, CuS (covelite) is a P-type (vacancy type) semiconductor material, and its formal oxidation state is (Cu + )3(S 2- )(S2 - ), the copper ion valence in CuS is +1. Preferably, in the Cu 2-x In S / Graphene composite absorbing materials, when x = 0.7 to 1, Cu 2-x The S / Graphene composite absorbing material has an electromagnetic wave reflection loss capability of -45 to -60 dB in the 8 to 10 GHz frequency band.

[0012] To achieve the above-mentioned purpose of the invention, the embodiment also provides a Cu 2-x The preparation method of S / Graphene composite wave absorbing material comprises the following steps:

[0013] (1) mixing a sulfur-containing precursor solution and a copper source, and washing the sample by centrifugation to prepare a CuS dispersion;

[0014] (2) preparing a graphene organic exfoliation solution by ultrasonic method;

[0015] (3) After mixing the graphene organic exfoliation solution and the CuS dispersion solution in a certain proportion, add the guest cation Cu 2+ and reducing agent, centrifuge and wash to obtain Cu 2-x S / Graphene composite absorbing material.

[0016] Preferably, in step (1), the sulfur-containing precursor solution is obtained by the following preparation method:

[0017] A certain amount of sulfur precursor is dissolved in an organic solvent, and an appropriate amount of oil-soluble surfactant is added, and then stirred and heated to 120-200°C at a heating rate of 5-15°C / min under vacuum, and kept warm for 30-60 minutes to form a completely dissolved sulfur-containing precursor solution, wherein the molar ratio of the organic solvent to the oil-soluble surfactant is 1:(0.8-1.2), the concentration of the sulfur-containing precursor solution is controlled at 2-5g / L, and the sulfur-containing precursor is selected from at least one of sulfur powder, sodium sulfide and hydrates thereof. Among them, the organic solvent is an octadecene organic solvent, and the oil-soluble surfactant is selected from one of oleyl dimethyl tertiary amine, oleic acid amine (oleic acid primary amine), and 1-aminooctane.

[0018] Preferably, in step (1), the sulfur-containing precursor solution and the copper source are mixed and centrifuged to prepare a CuS dispersion, comprising:

[0019] Inert gas is introduced into a reaction device containing a sulfur-containing precursor solution and a certain amount of copper source is added, wherein the molar ratio of Cu source / S source is <0.5, and then vacuum stirring is performed for 40 to 90 minutes, and after cooling to room temperature, the sample is centrifuged at 2500 to 5000 rpm for 3 to 10 minutes to obtain a CuS sample, and the CuS sample is dissolved in an organic solvent to form a CuS dispersion. The copper source is selected from at least one of copper acetate and its hydrate. The organic solvent is a toluene organic solvent.

[0020] Preferably, in step (2), the step of preparing the graphene organic exfoliation solution by ultrasonic method comprises:

[0021] The graphene is dissolved in an organic solvent, and a surfactant is added, and the mixture is stirred at room temperature for 30 to 60 minutes, and subjected to ultrasound for 60 to 120 minutes to form a graphene suspension. The graphene suspension is centrifuged at a speed of 1000 to 2000 rpm for 10 to 30 minutes, and the upper clear liquid is taken as a graphene organic stripping liquid; wherein the organic solvent of the graphene is selected from any one of ethylene glycol, dimethylformamide, methylpyrrolidone, and tetrahydrofuran; and the surfactant of the graphene is selected from any one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and polyethylene oxide-polypropylene oxide-polyethylene oxide.

[0022] Preferably, in step (3), after the graphene organic stripping solution and the CuS dispersion are mixed in a certain proportion, the guest cation Cu 2+ and reducing agent, centrifuge and wash to obtain Cu 2-x S / Graphene composite absorbing material, including:

[0023] The graphene suspension is added to the CuS dispersion according to the mass ratio of graphene to CuS of 1:(0.01-0.15), the reducing agent is added according to the molar ratio of CuS to reducing agent of 1:(3-10) and stirred for 20-60 minutes, and then the CuS and Cu dispersion is stirred for 20-60 minutes. 2+ The molar ratio of Cu is 1: (0.2-2) and the guest cation Cu is added. 2+ , stir the reaction for 2 to 10 minutes, centrifuge the sample at a speed of 8000 to 12000 rpm for 5 to 10 minutes, and then vacuum dry it at 150 to 220°C for 60 to 120 minutes to obtain Cu 2-x S / Graphene composite wave absorbing material, wherein the reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid and ethylene glycol.

[0024] To achieve the above-mentioned purpose of the invention, the embodiment also provides a Cu 2-x S / Graphene composite absorbing material, wherein the Cu 2-x The S / Graphene composite absorbing material is prepared according to the above preparation method.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] Taking full advantage of Cu 2-x The high dielectric properties of S nanoparticles and the high specific surface area and light weight of graphene were used to synthesize Cu with "thin, light, wide and strong" wave-absorbing properties through a simple chemical conversion preparation method. 2-x S / Graphene composite absorber, the Cu 2-x S / Graphene composite absorbing material can be used as a microwave absorber alone or as a functional material in combination with matrix materials such as paraffin. It has a good application prospect in the field of microwave electronic technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 is the Cu provided in the embodiment 2-x Flow chart of the preparation method of S / Graphene composite absorbing material;

[0029] Figure 2 is Cu in Example 1 of the present invention 1.125 XRD pattern of S / Graphene composite absorber;

[0030] Figure 3 is Cu in Example 1 of the present invention 1.125 TEM image of S / Graphene composite absorber;

[0031] Figure 4 is Cu in Example 1 of the present invention 1.125 Electromagnetic wave reflection loss diagram of S / Graphene composite absorber;

[0032] Figure 5 is Cu in Example 2 of the present invention 1.75 XRD pattern of S / Graphene composite absorber;

[0033] Figure 6 is Cu in Example 2 of the present invention 1.75 Electromagnetic wave reflection loss diagram of S / Graphene composite absorber. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. The implementation cases described are only some of the multiple possible embodiments in the present invention, rather than all of the embodiments, and are intended to provide a basic understanding of the present invention, and are not intended to confirm the key or decisive elements of the present invention or to limit the scope of protection. It is easy to understand that according to the technical solutions of the present invention, without changing the essential spirit of the present invention, a person of ordinary skill in the art can propose other interchangeable implementations. Therefore, the following specific implementation methods and drawings are only exemplary descriptions of the technical solutions of the present invention, and should not be regarded as the entirety of the present invention or as a definition or limitation of the technical solutions of the present invention.

[0035] Compared with the flake Cu disclosed in CN108862366A 2-xS nanocrystals, in order to further increase the Cu 2-x S nanocrystals to avoid Cu 2-x S nanocrystals agglomerate, a Cu 2-x S / Graphene composite absorber, using the high specific surface area of ​​Graphene, Cu 2-x S nanocrystals can be evenly distributed on the graphene surface, greatly improving the Cu 2- x Due to the dispersibility of S nanocrystals and the material interface polarization ability, the prepared composite absorber not only has excellent absorbing reflection loss performance, but also has a wider absorbing frequency band at -10dB reflection loss.

[0036] The Cu 2-x The S / Graphene composite absorber is composed of graphene organic solution, CuS dispersion and guest cation Cu 2+ The reaction yielded Cu 2-x S particles are uniformly attached to the monolayer 2D Graphene, where Cu 2-x The mass ratio of S to Graphene is 1:(0.01-0.15), and the value range of x is 0≤x≤1. 2+ / CuS to regulate the molar ratio of Cu 2-x The absorbing properties of S / Graphene composite absorbing material.

[0037] like Figure 1 As shown, the embodiment also provides a Cu 2-x The preparation method of S / Graphene composite wave absorbing material comprises the following steps:

[0038] Step 1, mixing a sulfur-containing precursor solution and a copper source, and washing the sample by centrifugation to prepare a CuS dispersion, comprising:

[0039] Inert gas is introduced into a reaction device containing a sulfur-containing precursor solution and a certain amount of copper source is added, followed by vacuum stirring and reacting for 40 to 90 minutes, cooling to room temperature, centrifuging and washing the sample at 2500 to 5000 rpm for 3 to 10 minutes to obtain a CuS sample, and dissolving the CuS sample in an organic solvent to form a CuS dispersion. The copper source is selected from at least one of copper acetate and its hydrate.

[0040] The sulfur-containing precursor solution is prepared by:

[0041] A certain amount of sulfur precursor is dissolved in an organic solvent, and an appropriate amount of oil-soluble surfactant is added, and then stirred and heated to 120-200°C at a heating rate of 5-15°C / min under vacuum, and kept warm for 30-60 minutes to form a completely dissolved sulfur-containing precursor solution, wherein the molar ratio of the organic solvent to the oil-soluble surfactant is 1:(0.8-1.2), and the concentration of the sulfur-containing precursor solution is controlled at 2-5g / L. The sulfur-containing precursor is selected from at least one of sulfur powder, sodium sulfide and hydrates thereof.

[0042] Step 2, preparing a graphene organic stripping solution by ultrasonic method, comprising the following steps:

[0043] The graphene is dissolved in an organic solvent, and a surfactant is added, and the mixture is stirred at room temperature for 30 to 60 minutes, and subjected to ultrasound for 60 to 120 minutes to form a graphene suspension. The graphene suspension is centrifuged at a speed of 1000 to 2000 rpm for 10 to 30 minutes, and the upper clear liquid is taken as a graphene organic stripping liquid; wherein the organic solvent of the graphene is selected from any one of ethylene glycol, dimethylformamide, methylpyrrolidone, and tetrahydrofuran; and the surfactant of the graphene is selected from any one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and polyethylene oxide-polypropylene oxide-polyethylene oxide.

[0044] Step 3: After mixing the graphene organic stripping solution and the CuS dispersion solution in a certain proportion, add the guest cation Cu 2+ and reducing agent, centrifuge and wash to obtain Cu 2-x S / Graphene composite absorbing material, including:

[0045] The graphene suspension is added to the CuS dispersion according to the mass ratio of graphene to CuS of 1:(0.01-0.15), the reducing agent is added according to the molar ratio of CuS to reducing agent of 1:(3-10) and stirred for 20-60 minutes, and then the CuS and Cu dispersion is stirred for 20-60 minutes. 2+ The molar ratio of Cu is 1: (0.2-2) and the guest cation Cu is added. 2+ , stir the reaction for 2 to 10 minutes, centrifuge the sample at a speed of 8000 to 12000 rpm for 5 to 10 minutes, and then vacuum dry it at 150 to 220°C for 60 to 120 minutes to obtain Cu 2-x S / Graphene composite wave absorbing material, wherein the reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid and ethylene glycol.

[0046] Based on the above preparation method steps, further description and elaboration are given below in conjunction with the accompanying drawings and specific embodiments.

[0047] Example 1

[0048] 0.096 g of graphene was added to a reaction bottle containing 213 ml of ethylene glycol organic solvent, and 0.096 g of hexadecyltrimethylammonium chloride surfactant was added after magnetic stirring for 30 minutes. The stirring was continued for 30 minutes and then ultrasonicated for 80 minutes to form a graphene suspension. The graphene suspension was then centrifuged at a centrifugal speed of 1000 rpm for 10 minutes, and the obtained supernatant was used as the graphene organic stripping liquid.

[0049] Take a new reaction flask with a capacity of 500 ml, add 100 ml of octadecene organic solvent and 100 ml of oil-based dimethyl tertiary amine surfactant, then weigh 0.64 g of sulfur powder and pour it into the reaction flask, and place the reaction flask on a heatable magnetic stirrer. Stir and heat to 150 ° C at a heating rate of 5 ° C / min under vacuum. After keeping warm for 30 minutes, introduce Ar gas into the reaction flask, weigh 1.995 g of copper acetate monohydrate and pour it into the reaction flask. After vacuuming, stir and react for 50 minutes, and then gradually cool to room temperature.

[0050] 40 ml of methanol was added to the reaction solution cooled to room temperature, and after stirring evenly, the reaction solution was centrifuged at 5000 rpm for 3 min. The CuS sample obtained by centrifugation was dissolved in 29 ml of toluene to obtain a CuS dispersion, and the CuS dispersion was added to the graphene organic stripping solution. Then, 8.800 g of ascorbic acid reducing agent was added to the graphene stripping solution, and after stirring until completely dissolved, the guest cation Cu was added. 2+ 0.399 g of copper acetate monohydrate was added, and the reaction was stopped after stirring for 3 min. The reaction solution was mixed with 240 ml of methanol and centrifuged at 12000 rpm for 5 min. The sample obtained by centrifugation was dried in an oven at 200 ° C for 150 min to obtain Cu 1.125 S / Graphene composite absorbing material.

[0051] Figure 2 is Cu in Example 1 of the present invention 1.125 XRD diagram of S / Graphene composite absorber, Figure 2 The X-ray diffraction peaks in the graphene (1 0 1) surface correspond to the diffraction peaks of the yazdrite Cu 1.125 The diffraction peaks of the S(0 0 22)(1 0 13)(1 1 1)(11 16)(1 1 24) planes are relatively weak because graphene is in a single-layer or double-layer state after exfoliation and has a low crystallinity. Figure 3 is Cu in Example 1 of the present invention 1.125 TEM image of S / Graphene composite absorber, from Figure 3 Cu can be seen in 1.125The S particles are evenly distributed on the graphene, making good use of the large specific surface area of ​​graphene, which helps Cu 1.125 S particles fully reflect and lose electromagnetic waves; Figure 4 is Cu in Example 1 of the present invention 1.125 Electromagnetic wave reflection loss diagram of S / Graphene composite absorber, from Figure 4 The Cu 1.125 The S / Graphene composite absorbing material has an electromagnetic wave reflection loss of less than -10dB with a bandwidth of up to 10GHz and a maximum reflection loss capability of -44.8dB. This absorbing material can be used in the field of microwave absorption that requires wide bandwidth and high electromagnetic wave reflection loss.

[0052] Example 2

[0053] 0.096 g of graphene was added to a reaction bottle containing 213 ml of ethylene glycol organic solvent, and 0.096 g of hexadecyltrimethylammonium chloride surfactant was added after magnetic stirring for 30 minutes. The stirring was continued for 30 minutes and then ultrasonicated for 80 minutes to form a graphene suspension. The graphene suspension was then centrifuged at a centrifugal speed of 1000 rpm for 10 minutes, and the obtained supernatant was used as the graphene organic stripping liquid.

[0054] Take a new reaction flask with a capacity of 500 ml, add 100 ml of octadecene organic solvent and 100 ml of oil-based dimethyl tertiary amine surfactant, then weigh 0.64 g of sulfur powder and pour it into the reaction flask, and place the reaction flask on a heatable magnetic stirrer. Stir and heat to 150 ° C at a heating rate of 5 ° C / min under vacuum. After keeping warm for 30 minutes, introduce Ar gas into the reaction flask, weigh 1.995 g of copper acetate monohydrate and pour it into the reaction flask. After vacuuming, stir and react for 50 minutes, and then gradually cool to room temperature.

[0055] 40 ml of methanol was added to the reaction solution cooled to room temperature, and after stirring, the reaction solution was centrifuged at 5000 rpm for 3 min. The sample obtained by centrifugation was dissolved in 29 ml of toluene and added to the graphene organic stripping solution. Then, 8.800 g of ascorbic acid reducing agent was added to the graphene stripping solution, and after stirring until completely dissolved, the guest cation Cu was added. 2+ 1.995 g of copper acetate monohydrate was added, and the reaction was stopped after stirring for 3 min. The reaction solution was mixed with 240 ml of methanol and centrifuged at 12000 rpm for 5 min. The sample obtained by centrifugation was dried in an oven at 200 ° C for 150 min to obtain Cu 1.75 S / Graphene composite absorbing material.

[0056] Figure 5 is Cu in Example 2 of the present invention1.75 The XRD pattern of S / Graphene composite absorber Figure 5 It can be seen that the X-ray diffraction shows the diffraction peak of graphene (1 0 1) surface and the copper pentathite Cu 1.75 The diffraction peaks of the S(16 0 0)(18 2 1)(12 81)(22 0 0)(0 8 6)(8 8 6) plane are relatively weak because the graphene is in a single-layer or double-layer state after exfoliation and its crystallinity is low. Figure 6 is Cu in Example 2 of the present invention 1.75 Electromagnetic wave reflection loss diagram of S / Graphene composite absorber, from Figure 6 It can be found that compared with Cu 1.125 S / Graphene composite absorber, Cu 1.75 The bandwidth of S / Graphene composite absorber is narrowed, and the maximum reflection loss capability is -25.2dB. This is because Cu 2+ The amount of Cu increases, resulting in 1.75 The carrier concentration in the S / Graphene composite absorber decreases, reducing the resonance loss of the carriers to the electromagnetic wave. This absorber can be individually adjusted in terms of chemical composition for specific frequency bands and specified electromagnetic wave reflection loss levels.

[0057] The specific implementation methods described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above is only the most preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A Cu 2-x The preparation method of S / Graphene composite absorbing material is characterized by: The following steps are involved: (1) dissolving a certain amount of sulfur-containing precursor in an organic solvent, adding an appropriate amount of an oil-soluble surfactant, and then stirring and heating to 120-200° C. at a heating rate of 5-15° C. / min under a vacuum state, and keeping the temperature for 30-60 minutes to form a completely dissolved sulfur-containing precursor solution, wherein the copper source is selected from at least one of copper acetate and its hydrate, mixing the sulfur-containing precursor solution and the copper source, and washing the sample by centrifugation to prepare a CuS dispersion; (2) preparing a graphene organic exfoliation solution by ultrasonic method; (3) After mixing the graphene organic stripping solution and the CuS dispersion solution at a mass ratio of graphene to CuS of 1:(0.01-0.15), adding the reducing agent at a molar ratio of CuS to the reducing agent of 1:(3-10) and stirring for 20-60 minutes, and then stirring at a molar ratio of CuS to CuS of 1:(3-10). 2+ The molar ratio of Cu is 1: (0.2-2) and the guest cation Cu is added. 2+ , stir the reaction for 2 to 10 minutes, centrifuge the sample at a speed of 8000 to 12000 rpm for 5 to 10 minutes, and then vacuum dry it at 150 to 220°C for 60 to 120 minutes to obtain Cu 2-x S / Graphene composite absorber, Cu 2-x S particles are uniformly attached to the monolayer 2D Graphene, where Cu 2-x The mass ratio of S to Graphene is 1:(0.01-0.15), and the value range of x is 0<x<1.

2. The Cu according to claim 1 2-x The preparation method of S / Graphene composite absorbing material is characterized by: In step (1), the molar ratio of the organic solvent to the oil-soluble surfactant is 1:(0.8-1.2), and the concentration of the sulfur-containing precursor solution is controlled at 2-5 g / L.

3. Cu according to claim 2 2-x The preparation method of S / Graphene composite absorbing material is characterized by: The sulfur-containing precursor is selected from at least one of sulfur powder, sodium sulfide and hydrates thereof.

4. The Cu according to claim 1 2-x The preparation method of S / Graphene composite absorbing material is characterized by: In step (1), the sulfur-containing precursor solution and the copper source are mixed and centrifuged to prepare a CuS dispersion, comprising: Inert gas is introduced into a reaction device filled with a sulfur-containing precursor solution and a copper source is added, wherein the molar ratio of Cu source / S source is <0.5, followed by vacuum stirring and reacting for 40 to 90 minutes, cooling to room temperature, and centrifuging and washing the sample at a speed of 2500 to 5000 rpm for 3 to 10 minutes to obtain a CuS sample, and dissolving the CuS sample in an organic solvent to form a CuS dispersion.

5. The Cu according to claim 1 2-x The preparation method of S / Graphene composite absorbing material is characterized by: In step (2), the step of preparing the graphene organic exfoliation solution by ultrasonic method comprises: The graphene is dissolved in an organic solvent, and a surfactant is added, and the mixture is stirred at room temperature for 30 to 60 minutes, and ultrasonicated for 60 to 120 minutes to form a graphene suspension, and the graphene suspension is centrifuged at a speed of 1000 to 2000 rpm for 10 to 30 minutes, and the upper clear liquid is taken as a graphene organic stripping liquid; Wherein, the organic solvent of graphene is selected from any one of ethylene glycol, dimethylformamide, methyl pyrrolidone and tetrahydrofuran; The surfactant of graphene is selected from any one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and polyethylene oxide-polypropylene oxide-polyethylene oxide.

6. The Cu according to any one of claims 1 or 5 2-x The preparation method of S / Graphene composite absorbing material is characterized by: The reducing agent is selected from at least one of hydrazine hydrate, ascorbic acid and ethylene glycol.

Citation Information

Patent Citations

  • Application of flake-like Cu2-xS nanocrystalline as microwave absorbent, and preparation method thereof

    CN108862366A

  • CuS / graphene nano composite material and preparation method thereof, and application in field of microwave absorption

    CN111943252A